Interspeech 2020 2020
DOI: 10.21437/interspeech.2020-2842
|View full text |Cite
|
Sign up to set email alerts
|

ASR-Based Evaluation and Feedback for Individualized Reading Practice

Abstract: Learning to read is a prerequisite to participate in our knowledge society. Developing reading skills requires intensive practice with individual evaluation and guidance by teachers, which is not always feasible in traditional classroom instruction. Automatic Speech Recognition (ASR) technology could offer a solution, but so far it has been mostly used to follow children while reading and to provide correct word forms through text-to-speech technology. However, ASR could possibly be employed at earlier stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…We investigated which words the children found to be most difficult to read and how the explicit feedback provided by the reading tutor contributed to improving reading accuracy and speed in these Dutch first graders. Improvements in reading accuracy and speed were seen in different types of exercises [9]. After analyzing the data of this first experiment, we saw that a higher agreement between the system's scores and the judgements assigned by a human annotator could be obtained by adjusting the measures and thresholds in the system [10].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…We investigated which words the children found to be most difficult to read and how the explicit feedback provided by the reading tutor contributed to improving reading accuracy and speed in these Dutch first graders. Improvements in reading accuracy and speed were seen in different types of exercises [9]. After analyzing the data of this first experiment, we saw that a higher agreement between the system's scores and the judgements assigned by a human annotator could be obtained by adjusting the measures and thresholds in the system [10].…”
Section: Introductionmentioning
confidence: 87%
“…In a previous study we reported on research aimed at developing a reading tutor for Dutch first graders that employs ASR to "listen" and give feedback on pupils' reading aloud [9]. This system also has the capability of storing user activities and ASR information on the server.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose we employed various metrics, including Cohen's Kappa, Matthews Correlation Coefficient (MCC), precision, recall and F-measures. The material used in the reading tutor contains four reading tasks designed with different goals and difficulty levels for first graders [2]. We also investigated the ASR accuracy in each reading task and different word types from two reading tasks which contain both words that are familiar to the first graders and new words.…”
Section: Introductionmentioning
confidence: 99%